KEPEMIMPINAN KEPALA SEKOLAH SEBAGAI UJUNG TOMBAK DALAM MEMPERBAIKI KWALITAS SEKOLAH - NI NYOMAN PERNI (GUNA WIDYA: JURNAL PENDIDIKAN HINDU, 2017)
Qualified teachers are required to have a deep and extensive knowledge of science in accordance with the field of science owned. One area of science that deserves attention is the science of Education. The existence of teachers as a sub-system of the field of study is actually very important to build a "humanity" of learners who not only build cognitive, but also effective and psychomotorikPengatasi and understand the problem of school is not a simple thing, but activities that require the ability to consider and establish alternative solutions Principal role will be effective, if always observe and implement: (1) the school continually adjusts to the current internal and external conditions, (2) able to coordinate and unite the efforts of all human resources towards the achievement of objectives, (3) human resource behavior (4) human resources is an essential component of overall organizational planning, (5) in the context of principals' management should be able to establish a harmonious relationship between school goals and existing human resource behavior, (6) in improving efektivi bag and school efficiency of human resources functionKeywords: Leadership and school quality